TaLAMP1 Plays Key Roles in Plant Architecture and Yield Response to Nitrogen Fertilizer in Wheat - Shi, Ji; Tong, Yiping (Frontiers in Plant Science, 2021)
Understanding the molecular mechanisms in wheat response to nitrogen (N) fertilizer will help us to breed wheat varieties with improved yield and N use efficiency. Here we cloned TaLAMP1-3A, -3B and -3D which were up-regulated in roots and shoots of wheat by low N availability. In a hydroponic culture, lateral root length and N uptake were decreased in both overexpression and knock-down of TaLAMP1 at seedling stage. In field experiment with normal N supply, grain yield of overexpression of TaLAMP1-3B is significantly reduced (14.5%) and knock-down of TaLAMP1 was significantly reduced (15.5%) .The grain number per spike of overexpression of TaLAMP1-3B was significantly increased (7.2%), but the spike number was significantly reduced (19.2%) compared with WT. While the grain number per spike of knock-down of TaLAMP1 was significantly decreased (15.3%), with no difference of the spike number compared with WT. Combined the agronomic data from field experiment of normal N and low N, both overexpression and knock-down of TaLAMP1 inhibited yield response to N fertilizer. Overexpressing TaLAMP1-3B greatly increased grain N concentration (GNC, 2.67%) with no significantly detrimental effect on grain yield under low N conditions, TaLAMP1-3B is therefore valuable in engineering wheat for low input agriculture. These results suggested that TaLAMP1 is critical for wheat adaptation to N availability, and in shaping plant architecture by regulating spike number per plant and grain number per spike. Optimizing TaLAMP1 expression may facilitate wheat breeding with improved yield, GNC and yield responses to N fertilizer.